Higher education and economic development in the OECD: policy lessons for other countries and regions. Issue 2 (3rd March 2016) - Pinheiro, Rómulo; Pillay, Pundy
ABSTRACT: This paper sheds light on the role of tertiary or higher education in economic development across two successful OECD case studies: Finland and South Korea. A number of key aspects are discussed, from the nature of the social contract between higher education and the economy to the endogenous characteristics of domestic higher education to the links between the sector and regional development, innovation and the labour market. The lessons learned are of importance to policy makers and institutional planners across the world, not least to less developing nations and regions, due to the unprecedented opportunities brought by a global, knowledge-based economy.